2015
DOI: 10.1039/c5cp05618g
|View full text |Cite
|
Sign up to set email alerts
|

Designing the topology of ion nano-channels in the mesophases of amphiphilic wedge-shaped molecules

Abstract: The wedge-shaped amphiphiles bearing sulfonate groups at the tip of the wedge are prone to form ion nano-channels upon exposure to a humid atmosphere. During swelling, water molecules preferentially accumulate in polar regions of the system resulting in the formation of a lyotropic phase. In this work, the details of the structure formation processes occurring upon swelling in water vapour, including determination of the size and topology of the ion nano-channels, are explored. The electron density profiles ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Эти фазы представляют собой органические цеолиты. Их главное преимущество заключается в наличии сети непрерывных каналов, которые могут быть исполь-зованы для различных практических применений (ион-обменных мембран, систем разделения, ката-лиза) [21]. Стоит подчеркнуть, что в образце сосуще-ствуют две кубические фазы, что предполагает их метастабильный характер.…”
Section: #8 / 70 / 2016unclassified
See 1 more Smart Citation
“…Эти фазы представляют собой органические цеолиты. Их главное преимущество заключается в наличии сети непрерывных каналов, которые могут быть исполь-зованы для различных практических применений (ион-обменных мембран, систем разделения, ката-лиза) [21]. Стоит подчеркнуть, что в образце сосуще-ствуют две кубические фазы, что предполагает их метастабильный характер.…”
Section: #8 / 70 / 2016unclassified
“…These phases are an organic zeolites. Their main advantage is the occurrence of a network of continuous channels that can be used for various practical applications (ionexchange membranes, separation systems, catalysis) [21]. It should be emphasized that two cubic phases coexist in the sample, which suggests their metastable nature.…”
Section: Fig2 Diffraction Patterns Of A-na At Rh = 33% (A) Rh = 50mentioning
confidence: 99%
“…In a previous work, we have shown how the use solvent-mediated lyotropic transitions can be used to tune the channel structure of the Na-derivative [23,24]. In the present paper, we focus on the effect of the counterion in the thermotropic phase behavior of the different mesophases as well as on their ion conducting properties.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, we have designed a series of wedge-shaped amphiphilic molecules containing a large hydrophobic rim and a hydrophilic sulfonic acid group at the focal point, which can self-assemble into lamellar and columnar structures [25][26][27][28][29][30]. It was further demonstrated that the complexes of poly(4-vinylpyridine) (P4VP) with wedge-shaped sulfonic acid molecules exhibited a liquid-crystalline lamellar phase at lower degrees of neutralization (DN), while formation of a hexagonal columnar mesophase was observed at higher DN [27].…”
Section: Introductionmentioning
confidence: 99%